(3bjO GdTQjO ef CNHGQ jRjOs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s ((3eMeO Hf eMehO GdYOhi GdeOYh HTeS GdOjf s)
(3ChdgG (B:s
(3GdMeO ddg eXgQ GdMb heHOjg s
(3Vefg CNHGQ jRjO Hf eYGhjI Hf CHj SajGfs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B118 s
Keywords: (3GdJGQjNs